MetaCity: ways of thinking and making city - Santos, S.; Ferreira, A. C. (2018)
Metacity launched the challenge of reflecting on the ‘implicit’ and mostly ‘invisible’ drivers that influence urban transformation. The call asked participants to explore the nexus between scientific knowledge, political and economic actors and social mobilization in the production of contemporary urban space. Questions were raised: What concepts, methods and fields of knowledge – instituted or to be established – can and will inform urban development theory(s) and practice(s) in the near future? What types of urban knowledge are still considered legitimate and what is their relevance? How public policies, governance practices and development strategies had change cities and how can we re-think these instruments? What, after all, is the effective importance of political and social mobilization of urban scientists and technicians in the process of “making cities”? We were pleased to received several contributions from different disciplines and geographies that have shown these are cross-cutting issues on a global scale. Some of these contributions were collected in this book and we will briefly present their main subjects.